ANALISIS MANAJEMEN SUMBER DAYA MANUSIA DALAM IMPLEMENTASI PEMBELAJARAN BERBASIS MEDIA DIGITAL - Ratu, Besse; Yusuf, Munir (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This study aims to determine the implementation of human resources in achieving digital media-based learning and the factors that support and hinder as well as solutions in overcoming the implementation of human resource management in achieving digital media-based learning at State Islamic Junior High School Wajo. This type of research is qualitative research and to obtain the data needed in this study, researchers used field research. The research location is State Islamic Junior High School Wajo, the research subjects are teachers and data collection uses observation, interview and documentation techniques. The results showed that human resources in implementing digital media must attend training and workshops. Human resource management in the implementation of digital media-based learning at State Islamic Junior High School Wajo uses smart tv and its impact is felt by students in teaching and learning activities. There is one factor that supports teaching and learning activities using smart tv namely facilities and infrastructure and one that hindersnamely the internet network. The solution to the inhibiting factor is to divert learning using power point. The use of smart tv greatly facilitates teachers and students in the learning process. Smart tv is a new breakthrough in education and learning becomes more effective and efficient.